Vision impairment and associated daily activity limitation: A systematic review and meta-analysis - Masoud Rahmati; Lee Smith; Laurent Boyer; Guillaume Fond; Dong Keon Yon; Hayeon Lee; Tarnjit Sehmbi; Mapa Prabhath Piyasena; Shahina Pardhan (PLoS ONE, 2025)
Background Vision impairment is a common disability that poses significant challenges to individuals’ ability to perform activities essential for independent living, including activities of daily living (ADL) and instrumental activities of daily living (IADL). Despite extensive research, the extent and nature of these associations remain unclear, particularly across varying levels and types of vision impairment. Objectives This meta‐analysis aims to estimate associations between vision impairment and difficulties with ADL and IADL. Methods We conducted a systematic review of relevant literature from the inception of the databases to February 2024, using electronic database searches, including PubMed, MEDLINE (Ovid), EMBASE, Cochrane CENTRAL, and CDSR. The articles were screened for title and abstract and then for the full-text reports by two independent reviewers and study quality was appraised. Meta‐analyses were performed using random effects models to calculate the pooled effect size, expressed as odds ratio (OR) with corresponding 95% confidence interval (CI) of each outcome. Results Forty-six studies involving 210,960 participants were included. A positive large correlation between vision impairment and difficulties with ADL (Correlation coefficient [r] = 0.55, 95% CI 0.37–0.68, p = 0.001) and IADL (r = 0.60, 95% CI 0.49–0.69, p = 0.001) was shown. We also found that vision impairment was associated with difficulties in ADL (OR = 1.77, 95% CI 1.56–2.01, p < 0.0001) and IADL (OR = 1.96, 95% CI 1.68–2.30, p < 0.0001). Subgroup analysis revealed that moderate to severe impairment resulted in difficulties in ADL (OR = 1.78, 95% CI 1.43–2.21, p = 0.02) and IADL (OR = 1.86, 95% CI 1.57–2.20, p = 0.0003). Further, there was a significant association between mild to moderate vision impairment and difficulties in IADL (OR = 1.38, 95% CI 1.23–1.55, p < 0.0001). Greater impact was observed in individuals with near vision impairment compared to those with distance vision impairment. Near vision impairment was significantly associated with higher difficulties in ADL (OR = 1.77, 95% CI 1.57–2.01, p < 0.0001) and IADL (OR = 1.79, 95% CI 1.32–2.42, p < 0.0001). In contrast, distance vision impairment showed lower but still significant associations with IADL (OR = 1.19, 95% CI 1.05–1.34, p = 0.005) and a nonsignificant association with ADL (OR = 1.12, 95% CI 0.90–1.40, p = 0.30). Meta-regression analysis indicated that for every one-year increase in age, ADL performance decreased by an average of 0.0147 units (p < 0.001), while IADL performance declined at a slower rate of 0.0047 units/year (p = 0.031). Conclusion The present systematic review and meta-analysis using several statistical methods indicates that vision impairment including near vision impairment, is associated with difficulties in ADL and IADL. Thus, vision impairment remains an urgent and increasingly important public health priority. These findings highlight the need for targeted measures to raise public health awareness to provide rehabilitation and eye care examination strategies to reduce the risk of developing disabilities in adults and the elderly who have vision impairment.